THE EFFECT OF KNOWLEDGE SHARING ON INNOVATIVE WORK BEHAVIOR: THE MODERATING ROLE OF LEADERSHIP AMONG MILLENNIAL CIVIL SERVANTS IN SOUTH SUMATRA, INDONESIA (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Innovation has become a strategic priority for public organizations in improving service quality and supporting bureaucratic reform in the digital era. As one of the largest workforce groups in government institutions, millennial civil servants are expected to demonstrate innovative work behavior by generating and implementing new ideas that enhance organizational performance. This study aims to examine the effect of knowledge sharing on innovative work behavior and investigate the moderating role of leadership among millennial civil servants in South Sumatra, Indonesia. A quantitative approach with an explanatory research design was employed using a survey of 200 respondents selected through purposive sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that knowledge sharing has a positive and significant effect on innovative work behavior (β = 0.472, t = 7.214, p < 0.001). Leadership also positively influences innovative work behavior (β = 0.318, t = 4.892, p < 0.001). Furthermore, leadership significantly strengthens the relationship between knowledge sharing and innovative work behavior (β = 0.201, t = 2.745, p = 0.006). The structural model explains 62.4% of the variance in innovative work behavior (R² = 0.624). These findings highlight the importance of fostering a knowledge-sharing culture and strengthening leadership practices to enhance innovation among millennial civil servants in the Indonesian public sector.